Familial Cancer Clustering in Urothelial Cancer: A Population-Based Case–Control Study. (8th December 2017) - Martin, Christopher; Leiser, Claire L; O'Neil, Brock; Gupta, Sumati; Lowrance, William T; Kohlmann, Wendy; Greenberg, Samantha; Pathak, Piyush; Smith, Ken R; Hanson, Heidi A
Abstract: Background: Family history of bladder cancer confers an increased risk for concordant and discordant cancers in relatives. However, previous studies investigating this relationship lack any correction for smoking status of family members. We conducted a population-based study of cancer risks in relatives of bladder cancer patients and matched controls with exclusion of variant subtypes to improve the understanding of familial cancer clustering. Methods: Case subjects with urothelial carcinoma were identified using the Utah Cancer Registry and matched 1:5 to cancer-free controls from the Utah Population Database. Cox regression was used to determine the risk of cancer in first-degree relatives, second-degree relatives, first cousins, and spouses. A total of 229 251 relatives of case subjects and 1 197 552 relatives of matched control subjects were analyzed. To correct for smoking status, we performed a secondary analysis excluding families with elevated rates of smoking-related cancers. All statistical tests were two-sided. Results: First- and second-degree relatives of case subjects had an increased risk for any cancer diagnosis (hazard ratio [HR] = 1.06, 95% confidence interval [CI] = 1.03 to 1.09, P < .001; HR = 1.04, 95% CI = 1.02 to 1.07, P = .001) and urothelial cancer (HR = 1.73, 95% CI = 1.50 to 1.99, P < .001; HR = 1.35, 95% CI = 1.21 to 1.51, P < .001). Site-specific analysis found increased risk for bladder (HR = 1.69, 95% CI = 1.47 to 1.95, P < .001), kidney (HR = 1.30, 95% CI = 1.08 to 1.57, P = .006), cervical (HR = 1.25, 95% CI = 1.06 to 1.49, P = .01), and lung cancer (HR = 1.34, 95% CI = 1.19 to 1.51, P < .001) in first-degree relatives. Second-degree relatives had increased risk for bladder (HR = 1.35, 95% CI = 1.2 to 1.5, P < .001) and thyroid cancer (HR = 1.18, 95% CI = 1.03 to 1.35, P = .02). Spouses showed an increased risk for laryngeal (HR = 2.68, 95% CI = 1.02 to 7.05, P = .04) and cervical cancer (HR = 1.57, 95% CI = 1.13 to 2.17, P = .007). These results did not substantively change after correction for suspected smoking behaviors. Conclusion: Our results suggest familial urothelial cancer clustering independent of smoking, with increased risk in relatives for both concordant and discordant cancers, suggesting shared genetic or environmental roots. Identifying families with statistically significant risks for non-smoking-related urothelial cancer would be extremely informative for genetic linkage studies.